Precarious Struggle to Criminalize Radicalization and Terrorism Doctrine Actions - Tantimin, Tantimin; Agustini, Shenti; Jaya, Febri; Tan, David (Jurnal Wawasan Yuridika, 2023)
Radicalism and terrorism are closely related as threats to peace and harmony, as bothare flawed manifestations of religious values and ideologies. The radicalization processcarried out by members of various terror organizations in Indonesia has not receivedmuch attention and hasn”™t been responded with concrete efforts to stop its spread asthe precursor to terrorism. The normative legal research method is used in this studyto analyze the positive elements and purposes of regulations related to the educationalsystem, free speech, and radicalism prevention in Indonesia. Findings of this studyillustrate the legal urgency in Indonesia to carry out normative construction regardingthe criminalization process of radicalization, as well as its limitations and obstacles,as part of the effort to prevent criminal acts of terrorism. As a point of prevention andresistance to the spread of radicalism and terrorism in Indonesia, this criminalizationprocess is juxtaposed with the existing education system.